Relationship between social cognition and fatigue, depressive symptoms, and anxiety in multiple sclerosis. Issue 2 (1st June 2019) - Genova, Helen M.; Lancaster, Katie; Lengenfelder, Jean; Bober, Christopher P.; DeLuca, John; Chiaravalloti, Nancy D.
Abstract : Emerging research indicates that in addition to physical and cognitive deficits, individuals with multiple sclerosis (MS) may also have impairments in social cognition, such as facial affect recognition and Theory of Mind (ToM). However, there is little research into how social cognition impairments relate to other domains in MS, such as mood and fatigue levels. The current study investigated whether social cognitive ability is associated with fatigue, depressive symptoms and anxiety in MS. Twenty‐eight individuals with MS completed questionnaires assessing fatigue (Modified Fatigue Impact Scale), depression (Beck Depression Inventory) and anxiety (State‐Trait Anxiety Inventory), as well as tasks of facial affect recognition and ToM (Reading the Mind in the Eyes; Strange Stories). Bivariate correlations were run to examine relationships between variables; partial correlations were subsequently used to ascertain whether these relationships persisted after controlling for cognitive ability (measured with the Symbol Digit Modalities Test). The results indicated that worse performance in both facial affect recognition and ToM were associated with higher rates of psychosocial fatigue, depressive symptoms, and anxiety levels; furthermore, these relationships were not explained by participants' cognitive ability. These preliminary results help us better understand the association between social cognitive abilities and other symptoms in MS, including depressive symptomatology, anxiety and fatigue.